Annual Plan 1994-95 Review and Outline Government of Manipur - Planning Commission (Planning Commission, 1993)
Manipur is a land locked State located in the easternmost part of the country. Nine-tenth of its total areas of 22,327 Sq.km, is in the hills and only one-tenth in the valley. The State does not have any waterways or effective railway transport system to link it with other parts of the country. The nearest rail heads are at Dimapur and Diribam, 215 and 222 kms.
Planning Department Government of Manipur